Electronic structure inspired a highly robust electrocatalyst for the oxygen-evolution reaction. Issue 58 (16th June 2020) - Zhang, Peng; Lu, Ying-Rui; Hsu, Chia-Shuo; Xue, Huai-Guo; Chan, Ting-Shan; Suen, Nian-Tzu; Chen, Hao Ming
Abstract : We demonstrated that the electronic-band structure holds the key to electrocatalytic durability towards the oxygen-evolution reaction (OER). Abstract : We demonstrated that the electronic-band structure holds the key to electrocatalytic durability towards the oxygen-evolution reaction (OER). Density functional theory (DFT) revealed the characteristic of Ni–Ni bonding interactions within Ni5 P4, Ni5 P2 and Ni3 P were different and could influence their phase stabilities during the OER. Ni5 P2 and Ni3 P exhibited very robust OER performances at high current density (>350 mA cm −2 ) over 12 h whereas, for Ni5 P4, obvious deterioration was observed. In situ / ex situ X-ray near-edge structure, high-resolution transmission electron microscopy, and X-ray photoelectron spectroscopy indicated the phase stability of Ni5 P4, Ni5 P2 and Ni3 P behaved differently during the OER. These materials transformed to Ni oxyhydroxide but the process for Ni5 P2 and Ni3 P was much slower even under high anodic potential 1.6 V (V vs. RHE). These results supported the theoretical prediction and provide a refreshing viewpoint for designing reliable electrocatalysts for the OER.